PENGARUH PENENTUAN PARAMETER PENGELASAN FCAW TERHADAP UKURAN LEG LENGTH FILLET WELD PADA MATERIAL ASTM A36 UNTUK MENINGKATKAN PRODUKTIVITAS - Popi Sasniati; Novebriantika; Hanifah Widiastuti; Reza Syahindra; Wiza Ulfa Fibarzi; Indah Retno Wulandary; Try Putra Lumbantoruan (Politeknik Negeri Batam, 2026)
Fillet weld on Tee Joint connections is commonly performed using a multipass technique to achieve the required leg length. However, specific leg length dimensions can also be achieved using a single-pass technique when welding parameters are properly selected. This study aims to investigate the effect of Flux Cored Arc Welding (FCAW) parameters on achieving fillet weld leg lengths of 6 mm, 7 mm, and 8 mm in a single pass on ASTM A36 steel. The welding process was carried out in the horizontal (2F) position with variations in welding current, voltage, and travel speed based on the Welding Procedure Specification (WPS). The results showed that a current range of 165–183 A, voltage of 23–24 V, and travel speed of 167–219 mm/min successfully achieved a 6 mm leg length; a current range of 185–225 A, voltage of 25–26 V, and travel speed of 280–315 mm/min achieved a 7 mm leg length; while a current range of 231–254 A, voltage of 27–29 V, and travel speed of 321–352 mm/min achieved an 8 mm leg length. The results of Visual Testing (VT), Magnetic Particle Inspection (MPI), and Macro Testing indicated that the welds were free from defects and complied with the applicable acceptance standards.